Social Capital, Cognition, and Entrepreneurial Opportunities: A Theoretical Framework - De Carolis, Donna Marie; Saparito, Patrick (Entrepreneurship Theory and Practice, 2006)
Entrepreneurship—the recognition and exploitation of opportunities—is valuable within organizations as well as in the establishment of new ventures. Some studies have addressed the issue why some individuals take advantage of opportunities and some do not. While some studies find that psychological variables, personality traits and demographic factors may distinguish entrepreneurial activity, these findings are equivocal. Other research has looked to the importance of social capital and network ties to new venture creation. Yet, there is little discussion regarding the possibility that social capital and personal factors interact and influence entrepreneurial behavior. Drawing from social cognitive theory (Augoustinos & Walker, 1995; Fiske & Taylor, 1984; Bandura, 1986; Wood & Bandura, 1989) this paper advances a model suggesting that entrepreneurial behavior is a result of the interplay of environments (i.e., social networks) and certain cognitive biases in entrepreneurs. We propose that both individual cognition and social capital are important in understanding entrepreneurial behavior. If the domain of entrepreneurship is “…the nexus of two phenomena: the presence of lucrative opportunities and the presence of enterprising individuals” (Shane & Venkataraman, 2000) then our model suggests an explanation of this nexus through exploring how both external (i.e., social capital) and internal factors (i.e., cognition) affect why some people and not others exploit opportunities.